CsPbBr3/Cs4PbBr6 perovskite@COF nanocomposites for visible-light-driven photocatalytic applications in water - Kour, Prachi; Mukherjee, Shatabdi Porel (Journal of Materials Chemistry A, 2021)
For the first time, we have synthesized all-inorganic CsPbBr3/Cs4PbBr6 perovskite@COF nanocomposites under atmospheric conditions and tuned the crystal structures of the perovskite as well. The nanocomposite is reasonably stable and maintains its crystalline properties even when dipped into water for 60 minutes. The perovskite@COF nanocomposite shows efficient visible-light-driven photocatalytic performance to degrade Methyl orange (10 mL; 20-100 ppm). The rate of photodegradation was about 0.245 min(-1) with high catalytic activity and recyclability for three to six cycles.

Organic-inorganic perovskitoid with zwitterion cysteamine linker and its crystal-crystal transformation to ruddlesden-popper phase - Kour, Prachi; Reddy, Mallu Chenna; Pal, Shiv; Sidhik, Siraj; Das, Tisita; Pandey, Padmini; Mukherjee, Shatabdi Porel; Chakraborty, Sudip; Mohite, Aditya D.; Ogale, Satishchandra (Angewandte Chemie-International Edition, 2021)
We demonstrate synthesis of a new low-D hybrid perovskitoid (a perovskite-like hybrid halide structure, yellow crystals, P21/n space group) using zwitterion cysteamine (2-aminoethanethiol) linker, and its remarkable molecular diffusion-controlled crystal-to-crystal transformation to Ruddlesden-Popper phase (Red crystals, Pnma space group). Our stable intermediate perovskitoid distinctly differs from all previous reports by way of a unique staggered arrangement of holes in the puckered 2D configuration with a face-sharing connection between the corrugated-1D double chains. The PL intensity for the yellow phase is 5 orders higher as compared to the red phase and the corresponding average lifetime is also fairly long (143 ns). First principles DFT calculations conform very well with the experimental band gap data. We demonstrate applicability of the new perovskitoid yellow phase as an excellent active layer in a self-powered photodetector and for selective detection of Ni2+ via On-Off-On photoluminescence (PL) based on its composite with few-layer black phosphorous.
Keywords: Crystal growth; organic-inorganic hybrid composites; perovskite phases; photodetectors; zwitterions

Lead-free low-dimensional tetraalkylammonium manganese- and copper-based hybrid organic–inorganic perovskites for visual fluorometric Pb2+ ion detection - Kour, Prachi; Sahu, Pragati; Dambhare, Neha V.; Rath, Arup Kumar; Mukherjee, Shatabdi Porel (ACS Applied Optical Materials, 2024)
For the first time, we have synthesized lead (Pb)-free manganese (Mn)- and copper (Cu)-based hybrid organic–inorganic perovskite (HOIP) compounds, compound 1, (TEA)2MnBr4, compound 2, (TBA)2MnBr4, compound 3, (TEA)2CuBr4, and compound 4, (TBA)CuBr2 (where TEA is tetraethylammonium and TBA is tetrabutylammonium), under ambient conditions via mechanochemical synthesis methodology using a Kakuhunter-made planetary mixer. The compounds are characterized as 2D except for (TBA)CuBr2, which has crystallized in the 0D lattice. The synthesized compounds are phase pure and show a stable solid-state emission at room temperature. The Mn-based perovskite compound 1 showed excellent environmental photostability for over a month and reasonable stability under a relative humidity of 70–80%. The nanoparticle (NP) dispersions of compounds 1 and 2 were used further for fluorescence titration studies using various heavy metal cations, including transition metals and lanthanides (e.g., Y3+, Nb3+, Co2+, Ni2+, Ag+, Zn2+, Cd2+, Pb2+, Gd3+, and Dy3+), where they showed good fluorescence switching by the Pb2+ ion. Compound 1 demonstrated excellent fluorescence switching performance with Pb2+ titration with a Pb2+ detection limit of 2.43 × 10–8 M and hence can be used to fabricate a Pb2+ calorimetric sensor. A preliminary visual thin film-based sensor using NPs of compound 1 was fabricated to test the change in emission from blue to green in correlation with the results obtained in the NP solution during Pb2+ ion sensing. A fascinating in situ ion-exchange-based mechanism for the sensitivity of NPs of compound 1 is confirmed. This study reveals the ability of Pb-free Mn-based HOIPs to detect an oxidizing metal cation, Pb2+, efficiently and quantitatively.